PENGARUH KOMPETENSI PEGAWAI DAN FASILITAS PERPUSTAKAAN TERHADAP KUALITAS PELAYANAN PADA DINAS PERPUSTAKAAN DAN KEARSIPAN DAERAH KOTA METRO PROVINSI LAMPUNG - Erna Fitri (SIMPLEX: Journal of Economic Management, 2021)
The library is a reading house provided by the Regional Library and Archives Office of Metro City, Lampung Province to increase knowledge and interest in reading. Although technological advances have made it easier for people to access online, the Regional Library and Archives Agency of Metro City, Lampung Province, is trying to provide quality services through adequate library facilities and is supported by the competence of employees in serving the public as library visitors. The formulation of the problem in this study, namely 1) Is there an effect of employee competence on service quality at the Regional Library and Archives Agency of Metro City, Lampung Province? 2) Is there an effect of employee facilities on service quality at the Regional Library and Archives Agency of Metro City, Lampung Province? 3) Is there an effect of employee competence and employee facilities together on the quality of service at the Regional Library and Archives Agency of Metro City, Lampung Province? This research was conducted at the Regional Library and Archives Agency of Metro City, Lampung Province. The sampling technique used purposive sampling to 90 respondents, namely library visitors both offline and online. The analysis technique in this research is using multiple linear regression test. From the results of the study, it can be concluded that the competence of employees and library facilities has a positive and significant effect on service quality either partially or simultaneously. This shows the quality of service can be formed well, if the human resource factor becomes quality. Although, in terms of services, it is not only a factor of human resources, there are still facilities and infrastructure to support it. However, there needs to be the formation of a strong relationship between each other and starting from the competence of employees